Application of the Principle of Equality Before the Law in Law Enforcement on Criminal Acts of Misuse and Distribution of Pharmacy Drugs Without a Permit (Study of Several Court Decisions) - Nur Fadillah Rizky Nasution; Mahmud Mulyadi; Vita Cita Emia Tarigan (International Conference on Health Science, Green Economics, Educational Review and Technology, 2025)
This study aims to determine and analyze the urgency of the principle of equality before the law in criminal law enforcement, to determine and analyze the differences in court decisions on criminal acts of abuse and distribution of pharmaceutical drugs without a permit according to the perspective of the principle of equality before the law, to determine and analyze the enforcement of criminal law in the future by Judges against criminal acts of distribution and abuse of pharmaceutical drugs without a permit in accordance with the principle of equality before the law. The method in this study uses a normative research type and descriptive research nature, with a legislative research approach and a case approach, supported by primary, secondary and tertiary data, as well as data collection tools through literature studies or document methods, which are obtained using qualitative analysis. The results of this study are that the urgency of the principle of equality before the law is, as a basic principle for achieving justice. The difference in sentences imposed by judges is due to the Judge having used a progressive view in sentencing the defendant, which is contained in each Judge's Consideration, and is in accordance with the concept of the principle of equality before the law. Criminal law enforcement in the future by Judges in accordance with the principle of equality before the law is that Judges in court must be able to fulfill what is demanded by justice seekers by continuing to base themselves on justice, certainty and legal benefits and in accordance with the school of natural law, Positivism, Sociological Jurisprudence, American Legal Realism, and Economic Analysis Of Law. Suggestions from the results of this study to law enforcers to consistently apply the principle of equality before the law, to the POM office to be more proactive in carrying out supervision of all drug distribution optimally throughout the region.